Patient H.M. : a story of memory, madness and family secrets - Dittrich, Luke (New York : Random House, 2016)
"In the summer of 1953, a renowned Yale neurosurgeon named William Beecher Scoville performed a novel operation on a 27-year-old epileptic patient named Henry Molaison, drilling two silver-dollar sized holes in his forehead and suctioning out a few teaspoons of tissue from a mysterious region deep inside his brain. The operation helped control Molaison's intractable seizures, but it also did something else: It left Molaison amnesic for the rest of his life, with a short term memory of just thirty seconds. Patient H.M., as he came to be known, would emerge as the most important human research subject in history. Much of what we now know about how memory works is a direct result of the sixty years of near-constant experimentation carried out upon him until his death in 2008. Award-winning journalist Luke Dittrich brings readers from the gleaming laboratory in San Diego where Molaison's disembodied brain -- now the focus of intense scrutiny -- sits today; to the surgical suites of the 1940s and 50s, where doctors wielded the powers of gods; and into the examination rooms where generations of researchers performed endless experiments on a single, essential, oblivious man: H.M. In the process, Dittrich excavates the lives of Dr. Scoville and his most famous patient, and spins their tales together in thrilling, kaleidoscopic fashion, uncovering troves of well-guarded secrets, and revealing how the bright future of modern neuroscience has dark roots in the forgotten history of psychosurgery, raising ethical questions that echo into the present day"--
Part I: Origins. The fall ; Crumpled lead and rippled copper ; Dream jobs ; The bridge ; Arline -- Part II: Madness. Pomander walk ; Water, fire, electricity ; Melius anceps remedium quam nullum ; The broken ; Room 2200 ; Sunset Hill ; Experiment successful, but the patient died ; Unlimited access ; Ecphory ; The vacuum and the ice pick -- Part III: The hunt. It was brought into the sea ; Proust on the operating table ; Fortunate misfortunes ; Henry Gustave Molaison (1926-1953) -- Part IV: Discovery. Where angels fear to tread ; Monkeys and men ; Interpreting the stars ; The son-of-a-bitch center ; The MIT research project known as the amnesic patient H.M. -- Part V: Secret wars. Dewey defeats Truman ; A sweet, tractable man ; It is necessary to go to Niagara to see Niagara Falls ; Patient H.M. (1953-2008) ; The smell of bone dust ; Every day is alone in itself ; Postmortem.
Includes index.
1 2
Keywords: H. M., -- 1926-2008.; Scoville, William Beecher, -- 1906-1984.; H. M., -- 1926-2008.; Scoville, William Beecher, -- 1906-1984.; H. M., -- 1926-2008.; Scoville, William Beecher, -- 1906-1984.; H. M., -- 1926-2008.; Scoville, William Beecher, -- 1906-1984.; Amnesiacs -- Biography; Epilepsy -- Surgery -- United States -- History; Memory disorders -- Patients; Frontal lobotomy -- History; Brain -- Surgery -- United States -- History; Epilepsy -- Surgery -- United States -- History; Epilepsy -- surgery; Amnesia, Anterograde; Epilepsy -- surgery; Memory Disorders; Memory, Long-Term.; Amnesiacs; Brain -- Surgery; Epilepsy -- Surgery; Frontal lobotomy; Memory disorders -- Patients; United States; Neurochirurgie; Hirnforschung; Amnesia; Epilepsy -- Surgery; Memory disorders; Memory; Biography; Biographies; Biography; History; Biographies; Biographies; Biography